Overexpression of cMOAT (MRP2/ABCC2) is associated with decreased formation of platinum-DNA adducts and decreased G2-arrest in melanoma cells resistant to cisplatin - Liedert, Bernd; Schadendorf, Dirk (The journal of investigative dermatology, 2015)
Resistance to various anti-neoplastic agents is a common observation in clinical management of melanoma. The biologic mechanisms conferring these different drug-resistant phenotypes, including resistance against the commonly used anti-cancer drug cisplatin, are unclear. In order to elucidate the role of the membrane adenosine triphosphate binding cassette-transporter cMOAT (canalicular multispecific anion transporter) (MRP2/ABCC2) in cisplatin resistance of melanoma, the expression of this protein was analyzed in the platinum drug-resistant cell line MeWo CIS 1. Cisplatinresistant melanoma cells showed a distinct overexpression of cMOAT on mRNA and protein level. This observation was accompanied by a reduced formation of platinum-induced intrastrand cross-links in the nuclear DNA measured by an immunocytologic assay. This decrease in DNA platination was accompanied by an accelerated re-entry into the cell cycle after the typical cisplatin-induced G2 arrest, and a resistance to undergo apoptosis. Kinetics of formation and elimination of platinum-DNA adducts suggest that the DNA repair capacity for Pt-d(GpG) adducts was not elevated in platinum drug-resistant melanoma cells. The decrease in platinum-DNA adduct formation in cisplatin-resistant melanoma cells was rather a reflection of the protecting activity of the transporter cMOAT. In conclusion, the functional inhibition of cMOAT might be a promising strategy in the reversal of resistance to platinum-based anti-cancer drugs in human melanoma.